2012
DOI: 10.1037/a0027161
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of perinatal essential fatty acid deficiency on anxiety-related behavior in mice.

Abstract: Dietary essential fatty acids have been shown to regulate behavioral and cognitive functions in rodents. However, the long-term effect on behavior, besides memory and learning, of essential fatty acid deficiency (EFAD), i.e., lack of n-3 and n-6 fatty acids, during the perinatal period has not been investigated. Therefore, pregnant C57Bl/6 mice were given either an EFAD or an isoenergetic control diet from gestational day 16 and throughout lactation. The female offspring were given standard chow from 3 weeks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
4
0
1
Order By: Relevance
“…Supplementation with N-3 LCPUFA enhanced n-3 DHA content in the brain, mainly at the expense of n-6 AA and DTA. LCPUFA, in particular AA and DHA (Palsdottir et al, 2012), are incorporated in the neuronal cell membrane to maintain normal brain function (Schuchardt et al, 2010;Bourre et al, 1991;Uauy and Dangour, 2006). Brain fatty acid content is dependent on nutritional intake and it was shown that suboptimal n-3 LCPUFA intake during gestation and postnatal development caused neurodevelopmental deficits in preclinical (Chen and Su, 2013;Bhatia et al, 2011) and clinical studies (Birch et al, 2000;Willatts et al, 1998;Drover et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with N-3 LCPUFA enhanced n-3 DHA content in the brain, mainly at the expense of n-6 AA and DTA. LCPUFA, in particular AA and DHA (Palsdottir et al, 2012), are incorporated in the neuronal cell membrane to maintain normal brain function (Schuchardt et al, 2010;Bourre et al, 1991;Uauy and Dangour, 2006). Brain fatty acid content is dependent on nutritional intake and it was shown that suboptimal n-3 LCPUFA intake during gestation and postnatal development caused neurodevelopmental deficits in preclinical (Chen and Su, 2013;Bhatia et al, 2011) and clinical studies (Birch et al, 2000;Willatts et al, 1998;Drover et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Brain lipid profile (rat). Brain lipid profile, adapted from Palsdottir et al (2012). C18:0: stearic acid; C18:2, n-6: linoleic-acid (LA); C20:3, n-6: Dihomo-gamma-linolenic acid (DGLA); C20:4, n-6: arachidonic acid (AA); C22:5, n-6: Docosapentaenoic acid (DPA); C18:3, n-3: Alpha-linolenic acid (ALA); C20:5, n3: Eicosapentaenoic acid (EPA); C22:5, n-3: Docosapentaenoic acid (DPA); C22:6, n-3: Docosahexaenoic acid (DHA).…”
Section: Function Of N-3 Pufamentioning
confidence: 99%
“…These studies are summarized in Table 1 for experimental rodent models and in Table 2 for experimental and observational studies in humans. In experimental rodent models, deficient levels of DHA during pregnancy resulted in deficits in learning, such as habituation to novelty and latency to reach learning criteria 50 ; prolonged corticosterone response to restraint stress and longer periods of immobility during the Porsolt forced swim test 51 ; and less exploration of environmental stimuli in the offspring, 52 as determined via tests designed to assess constructs similar to distress disorders in humans. Takeuchi et al 41 demonstrated that pups of DHA-deficient dams spent less time in the open arms of a plus maze (indicative of higher stress levels) than the offspring of normally fed animals.…”
Section: Evidence For An Association Between Docosahexaenoic Acid Levmentioning
confidence: 99%